The legislative framework of environmental impact assessments for establishment of ski resorts in mountainous areas - Douka A.; Stergiadou A. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
A strategy for the sustainable development of mountainous areas necessarily involves the development of the natural environment. Any intervention in the natural environment has to comply with the basic established principles of forestry and environmental law (sustainable management of forests).The absence of a comprehensive legal framework in Greece, which would describe with clarity, sufficient detail and accuracy the technical specifications for developing environmental impact assessments (EIA) lead researchers to form general conclusions according to the environmental compatibility of projects. Therefore, the improvement of legislation with objective, scientific criteria to be taken into account by researchers carrying out environmental impact assessments is essential. The aim of the present study is the examination and evaluation of the objectivity, coherence and completeness of the legal framework of developing environmental impact assessments for establishment of ski resorts in mountain grasslands in comparison with European standards.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)